2014
DOI: 10.1002/chem.201404555
|View full text |Cite
|
Sign up to set email alerts
|

Functional Carbazole Liquid‐Crystal Block Codendrimers with Optical and Electronic Properties

Abstract: The synthesis and characterisation of a family of block codendrimers consisting of highly versatile mesogenic and carbazole-containing 2,2-bis(hydroxymethyl)propionic acid (bis-MPA) dendrons are reported. The liquid-crystal behaviour was investigated by means of differential scanning calorimetry, polarised-light optical microscopy and X-ray diffraction. Depending on the chemical structure of the constituent dendrons, the codendrimers show lamellar or columnar mesophases. On the basis of the experimental result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 64 publications
(61 reference statements)
0
15
0
Order By: Relevance
“…Iguarbe, V. et al reported the synthesis of the Percectype mesogenic units, were prepared by a previously described method [30]. The synthesis of the Janus dendrimers was carried out by the coupling of the mesogenic block and carbazole-containing.…”
Section: Synthesis Of New Dendrimers Containing Carbazole With Liquid Crystalline Optical and Electrochemical Properties [28]mentioning
confidence: 99%
“…Iguarbe, V. et al reported the synthesis of the Percectype mesogenic units, were prepared by a previously described method [30]. The synthesis of the Janus dendrimers was carried out by the coupling of the mesogenic block and carbazole-containing.…”
Section: Synthesis Of New Dendrimers Containing Carbazole With Liquid Crystalline Optical and Electrochemical Properties [28]mentioning
confidence: 99%
“…This effect has already been observed in pure compounds where carbazole groups tend to prevent the formation of mesophases. 40 The driving forces for the gel formation were evaluated by studying the dendrons 1 and 2 by NMR at variable temperature. In the case of 1 only p-p, dipole-dipole and van der Waals interactions occur in the gel phase because all proton signals slightly shi to lower elds with increasing temperatures [45][46][47] ( Fig.…”
Section: Gel Formation Studiesmentioning
confidence: 99%
“…[36][37][38][39] In our previous work, the synthesis of a family of block codendrimers that combine liquid crystalline and optoelectronic properties was reported. 40 Given the molecular structure of these macromolecules, the formation of a supramolecular network in the presence of an organic solvent can be envisaged, and will be favoured by intra-and intermolecular interactions between different regions of the molecules. These molecules are one of the few examples of codendritic organogels.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, multiple functionalities can also be installed onto the periphery of dendrons for exhibiting versatile properties [10][11][12][13][14][15][16][17]. Surprisingly, though dendrimers as mesogens in liquid crystals have been extensively investigated because of their uniform packing and non-grained boundaries in the LC states [18][19][20][21][22][23][24][25][26][27][28][29][30], dendrons in the related studies are rather limited [31][32][33][34][35]. Possibly, dendrimers are rather symmetrical in chemical structures, which is advantageous for the easy formation of columnar phases [36][37][38][39][40][41][42][43][44][45][46][47][48][49].…”
Section: Introductionmentioning
confidence: 99%